Continuous Dependence For Benjamin-Bona-Mahony-Burger Equation - Zeynep Sümeyye Çelik; Şevket Gür (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this work, it is proved that the solutions ofBenjamin-Bona-Mahony-Burger equation depends continuously on the coefficients.